Characterization of a 3 alpha-hydroxysteroid dehydrogenase/carbonyl reductase from the gram-negative bacterium Comamonas testosteroni. - Oppermann, U; Maser, E (1996)
A new form of the NAD(P)-dependent 3 alpha-hydroxysteroid dehydrogenases (3 alpha-HSDs), present in the gram-negative bacterium Comamonas testosteroni ATCC 11996, was isolated from a testosterone-induced bacterial extract and characterized. The enzyme (HSD 28) has a monomeric molecular mass of 28 kDa. It belongs to the protein superfamily of short-chain dehydrogenases/reductases (SDR) as established by N-terminal sequence analysis. Along with the 3 alpha-hydroxysteroid dehydrogenase and 3-oxo-reductase activities towards a variety of cis or trans fused A/B ring steroids, it also reduces several xenobiotic carbonyl compounds, including a metyrapone-based class of insecticides, to the respective alcohol metabolites. No dihydrodiol dehydrogenase activity towards trans- or cis-benzene-dihydrodiols could be detected, thus distinguishing it from the indomethacine-sensitive, mammalian liver type 3 alpha-HSDs. Subcellular fractionation revealed that the enzyme is localized in the cytoplasm of the bacterial cell. Proteins similar to the 3 alpha-HSD were detected and characterized from Comamonas testosteroni strain ATCC 17454 and from a commercially available steroid-induced extract of a patent Pseudomonas strain. The N-terminal amino acid sequence of the 3 alpha-HSD from the latter strain (HSD 29) is highly similar (94% identity over 15 residues) to a previously determined primary structure of a Pseudomonas species 3 alpha-HSD. However, no similarities could be detected between HSD 28 and a recently determined 3 alpha-HSD sequence from the ATCC 11996 Comamonas strain. The specific crossreaction of antibodies directed against mammalian liver type I 11 beta-hydroxysteroid dehydrogenase (11 beta-HSD I) with the isolated 3 alpha-HSDs suggests the existence of a functionally and structurally related subgroup within the SDR superfamily. The broad substrate specificities of the characterized 3 alpha-HSD enzymes lead to the conclusion that they might participate in the intestinal bioactivation or inactivation of hormones, bile acids and xenobiotics since Comamonas testosteroni and related species are found in the intestinal tract of vertebrates including man.